Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.2337/db06-0251
|View full text |Cite
|
Sign up to set email alerts
|

α-Lipoic Acid Prevents the Increase in Atherosclerosis Induced by Diabetes in Apolipoprotein E–Deficient Mice Fed High-Fat/Low-Cholesterol Diet

Abstract: Considerable evidence indicates that hyperglycemia increases oxidative stress and contributes to the increased incidence of atherosclerosis and cardiovascular complications in diabetic patients. To examine the effect of ␣-lipoic acid, a potent natural antioxidant, on atherosclerosis in diabetic mice, 3-month-old apolipoprotein (apo) E-deficient (apoE ؊/؊ ) mice were made diabetic by administering streptozotocin (STZ). At 4 weeks after starting the STZ administration, a high-fat diet with or without ␣-lipoic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 49 publications
3
60
0
1
Order By: Relevance
“…It does so by activating the enzyme transketolase. α-Lipoic acid, a potent antioxidant, has also been reported to reduce diabetic microvascular and macrovascular complications in animal models [4,5]. To determine whether benfotiamine in combination with α-lipoic acid would normalise markers of reactive oxygen species-induced pathways of complications in humans, we performed a pilot study in participants with type 1 diabetes using one daily dose of benfotiamine in combination with α-lipoic acid.…”
Section: Introductionmentioning
confidence: 99%
“…It does so by activating the enzyme transketolase. α-Lipoic acid, a potent antioxidant, has also been reported to reduce diabetic microvascular and macrovascular complications in animal models [4,5]. To determine whether benfotiamine in combination with α-lipoic acid would normalise markers of reactive oxygen species-induced pathways of complications in humans, we performed a pilot study in participants with type 1 diabetes using one daily dose of benfotiamine in combination with α-lipoic acid.…”
Section: Introductionmentioning
confidence: 99%
“…␣-Lipoic acid is an important mitochondrial antioxidant, and supplementation was shown to decrease atherosclerosis in hyperlipidemic, diabetic mice (2036). Heterozygous deficiency of lipoic acid synthase in diabetic mice resulted in a 48% increase in atherosclerosis extent (1111).…”
Section: Consequences Of Ros Overproduction: Genetic Damagementioning
confidence: 99%
“…Further, DHLA has shown capability in regenerating reduced levels of exogeneous antioxidants such as tocopherols and vitamin C [Packer et al, 1995 [Kim et al, 2004]. In a study with LA supplementation for 20 weeks, it has been shown to prevent the increase of plasma total cholesterol and atherosclerotic lesions induced by diabetes in apolipoprotein E-deficient mice fed with high fat-low cholesterol diet [Yi & Maeda, 2006]. It has been further demonstrated that LA reduced atherosclerotic plaques in the abdominal aorta in hyperlipidemic rabbits with established atherosclerosis [Ying et al, 2010].…”
Section: Introductionmentioning
confidence: 99%